Achievements, priorities and strategies in pediatric nephrology in Europe: need for unifying approaches or acceptance of differences? - Ehrich, Jochen; Tasic, Velibor; Edvardsson, Vidar O.; Preka, Evgenia; Prikhodina, Larisa; Stefanidis, Constantinos J.; Topaloglu, Rezan; Shtiza, Diamant; Sarkissian, Ashot; Mueller-Sacherer, Thomas; Fataliyeva, Rena; Kazyra, Ina; et al. (FRONTIERS MEDIA SA, 2025)
Background There is a lack of information on the current healthcare systems for children with kidney diseases across Europe. The aim of this study was to explore the different national approaches to the organization and delivery of pediatric nephrology services within Europe.
Methods In 2020, the European society for Paediatric Nephrology (ESPN) conducted a cross-sectional survey to identify the existing pediatric nephrology healthcare systems in 48 European countries covering a population of more than 200 million children.
Results The reported three most important priorities in the care of children with kidney diseases were better training of staff, more incentives for physicians to reduce staff shortages, and more hospital beds. Positive achievements in the field of pediatric nephrology included the establishment of new specialized pediatric nephrology centers, facilities for pediatric dialysis and transplant units in 18, 16, and 12 countries, respectively. The most common problems included no access to any type of dialysis (12), inadequate transplant programs for all ages of children (12), lack of well-trained physicians and dialysis nurses (12), inadequate reimbursement of hospitals for expensive therapies (10), and lack of multidisciplinary care by psychologists, dieticians, physiotherapists, social workers and vocational counsellors (6). Twenty-five of 48 countries (52%) expected to have a shortage of pediatric nephrologists in the year 2025, 63% of clinical nurses and 56% of dialysis nurses. All three groups of health care professionals were expected to be lacking in 38% of countries. Prenatal assessment and postnatal management of renal malformations by a multidisciplinary team including obstetricians, geneticists, pediatricians, and pediatric surgeons was available in one third of countries.
Conclusions Our study shows that there are still very marked differences in pediatric health care systems across the European countries and highlights the need need for appropriate services for children with kidney disease in all European countries.